Surgical assessment clinic - One stop emergency out-patient clinic for rapid assessment, reduced admissions and improved acute surgical service: A quality improvement study. (November 2017) - Macano, Christina A.W.; Kirby, George C.; Lake, Blossom; Nyasavajjala, Sitaramachandra M.; Clarke, Robert
Abstract: Background: There is increasing pressure on emergency services within the NHS requiring efficient, rapid assessment and management of patients. A subsequent reduction in hospital admissions reduces overall costs with an aim to improve quality of care. At the Royal Shrewsbury Hospital we run a one stop emergency surgical clinic. With strict criteria for admission to this clinic we have established a care pathway for those patients requiring urgent surgical review but not necessarily hospital admission. Materials and methods: We reviewed our initial referral pathway to the emergency surgical assessment clinic. New guidelines were distributed to the local Care Coordination Centre (CCC) through which GP referrals to the clinic were made. A re-audit carried out 6 weeks later assessed change in clinical practice. Results: With the introduction of guidelines for referral we significantly increased the percentage of appropriate referrals to the one stop emergency surgical clinic (42.9%–79.4%, p = 0.000017). The majority (75.8%) of appropriate referrals can be successfully managed on an urgent outpatient basis. Appropriate referrals unsuitable for discharge from clinic had genuine reasons for admission such as abnormal results on assessment, or a need for surgery. 97.8% of referrals not deemed appropriate for the clinic were admitted for inpatient management. Conclusion: By providing suitable guidance for referring practitioners we have optimised our clinic use significantly and improved our acute ambulatory surgical care. We have reduced admissions, provided rapid treatment and have established a service that helps address the ever increasing demand on acute services within the NHS. Highlights: Most emergency surgery patients can be initially managed on an urgent outpatient basis. Guidelines for referral to an emergency surgical clinic reduces inappropriate referrals. An ambulatory care clinic reduces hospital admission.